Improving Governance and Fighting Corruption in the Baltic and CIS Countries : The Role of the IMF - Gurgen, Emine; Wolf, Thomas (Washington, D.C. : International Monetary Fund, 2000)
This paper examines the indirect role the IMF plays in combating corruption in the Baltic and CIS countries by promoting structural reforms that help improve economic governance and thus reduce opportunities for rent-seeking behavior. The analysis draws on examples of actual experience with corruption and outlines some of the structural measures under IMF-supported arrangements, which, if successfully implemented, can be expected to help gradually alleviate corruption. It also summarizes IMF-wide initiatives under way to strengthen public sector transparency and accountability, and highlights the key structural areas likely to receive emphasis in the IMF's future policy advice to countries in the region.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet